Consumer Behavior and Halal Cosmetic Product: Evidence in Palembang City - Senjawati Retno; . Suhel; Asngari Imam (Модернизация, инновация, развитие)
Purpose: this research is about the impact of the product quality, price, halal labeling, and brand ambassador for the purchasing decision of halal cosmetics product.Methods: the research samples involves 400 female respondents with age 20–49 based on income category, education and kinds of jobs in Palembang city, analysis using the Logit Analysis Method.Results: (1) the probability of the dominant factor in affecting the purchasing decision of the halal cosmetics product namely price; (2) the product quality, income, halal labeling, and brand ambassador have positive and significant impact; (3) the price has negative and significant impact for the purchasing decision of the purchasing decision of the cosmetics product.Conclusions and Relevance: overall, there are five potential factors which affect the purchase of the halal cosmetic product. This important aspect should be attention in the cosmetics halal purchase, because it is not only about the price but also the religiosity aspect such as knowledge, attitude, Islamic brand and subjective norm before deciding to buy the product.